Experimental Study for μ-class Control of Relative Position and Attitude for Synthetic Aperture Telescope Using Formation Flying Micro-satellites. Issue 2 (2020) - Suzumoto, Ryo; Ikari, Satoshi; Miyamura, Norihide; Nakasuka, Shinichi
Abstract: Earth remote sensing from geostationary orbit (GEO) realizes high time resolution that is essential for disaster monitoring; however, the spatial resolution is commonly worse than observation from low Earth orbit (LEO). In order to achieve high-resolution and high-frequency GEO remote sensing, we have proposed a "Formation Flying Synthetic Aperture Telescope (FFSAT)" with multiple micro-satellites. The FFSAT can improve the spatial resolution by using the technique of a synthetic aperture, and therefore the relative positions and attitudes between the optical units of each satellite must be controlled with an accuracy better than 1/10 of the observation wavelength. In order to verify feasibility of such highly accurate control, μ-class control experiments were conducted by using COTS components, and numerical models of the components were constructed. Results of the experiments were integrated into a software simulator, and the μ-class formation flying control of the entire FFSAT system was numerically evaluated. In this simulation, highly accurate control was achieved with dual-stage actuators, which consist of piezo actuators and thrusters. The simulation results show that the formation can be controlled in μ-class accuracy under some assumptions.